2001
DOI: 10.1039/b103242a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a new cage ligand, SarAr, and its complexation with selected transition metal ions for potential use in radioimaging†

Abstract: A new hexaazamacrobicyclic cage ligand, 1-N-(4-aminobenzyl)- 3,6,10,13,16,19-hexaazabicyclo[6.6.6]eicosane-1,8-diamine (SarAr) has been designed for conjugation to proteins. SarAr was synthesised and characterised by microanalyses, 1 H NMR and electrospray mass spectrometry. The complexation of selected transition metal ions (Cu(), Ni() and Co() at 10 Ϫ6 M) by SarAr was complete within 30 min over pH 6 to 8. The [ 64 Cu(SarAr)] 2ϩ complex was investigated with a view to applications in radioimaging. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
135
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(139 citation statements)
references
References 16 publications
4
135
0
Order By: Relevance
“…The [ 64 Cu(SarAr)] 2ϩ complex is rapidly excreted through the kidneys and, in contrast to other chelating agents, was not found to release copper into the liver (13). In the present study, we have extended these findings, showing tumor-specific uptake of SarAr-conjugated 64 Cu-labeled antineuroblastoma antibodies 14.G2a and ch14.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…The [ 64 Cu(SarAr)] 2ϩ complex is rapidly excreted through the kidneys and, in contrast to other chelating agents, was not found to release copper into the liver (13). In the present study, we have extended these findings, showing tumor-specific uptake of SarAr-conjugated 64 Cu-labeled antineuroblastoma antibodies 14.G2a and ch14.…”
Section: Discussionsupporting
confidence: 70%
“…Earlier work with unconjugated SarAr showed that [ 64 Cu(SarAr)] 2ϩ complexes were stable in plasma, with no significant dissociation of the complex after 174 h (13). The [ 64 Cu(SarAr)] 2ϩ complex is rapidly excreted through the kidneys and, in contrast to other chelating agents, was not found to release copper into the liver (13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also included 2-benzyl-3-methylisothiocyanato-diethylenetriaminepentaaceticacid (2B3M-ITC-DTPA) and a sarcophagine ligand, (1-NH 2 -8-NHCO(CH 2 ) 3 CO 2 H)sar where sar = sarcophagine = 3,6,10,13,16,19-hexaazabicyclo[6.6.6]icosane (sar-CO 2 H) 45,46 . Encapsulating hexaamine sarcophagine ligands, first prepared by Sargeson and coworkers [47][48][49][50][51] , form extraordinary stable complexes with copper(II) and benefit from rapid complexation rates 52,53 . Methods have been developed to introduce reactive functional groups to the ligand framework [54][55][56] , to allow the ligands to be conjugated to peptides and antibodies with a goal of synthesizing copper radiopharmaceuticals that benefit from the special properties of sarcophagine ligands 21,45,46,[57][58][59][60][61] .…”
Section: Introductionmentioning
confidence: 99%